Swiss Learning Health System: A national initiative to establish learning cycles for continuous health system improvement. Issue 3 (21st June 2018) - Boes, Stefan; Mantwill, Sarah; Kaufmann, Cornel; Brach, Mirjam; Bickenbach, Jerome; Rubinelli, Sara; Stucki, Gerold
Abstract: The health system in Switzerland is considered as one of the best in the world. Nevertheless, to effectively and efficiently meet current and future challenges, an infrastructure and culture are needed where the best evidence is systematically made available and used, and the system evolves on the basis of a constant exchange between research, policy, and practice. The Swiss Learning Health System institutionalizes this idea as a multistakeholder national initiative to ensure continuous improvement through ongoing research and implementation. This article presents the objectives and mechanisms of the Swiss Learning Health System in the context of international initiatives to strengthen health systems and improve population health through learning cycles.